Age, growth, mortality and sex ratio of the inshore population of the edible crab, Cancer pagurus (Linnaeus 1758) in South Wales (UK). (10th January 2013) - Klaoudatos, D. S.; Conides, A. J.; Anastasopoulou, A.; Dulčić, J.
Summary Age, growth, and mortality of the edible crab, Cancer pagurus, were determined for the native population in South Wales (UK). Sampling was carried out on a monthly basis between February 2001 and September 2002. Carapace width ranged between 10.4 and 163 mm. Based on the carapace width frequency distribution, the Swansea and Gower population was composed mainly of males belonging to the first and second age‐class (1 and 2), and of females belonging to the third and fourth age‐class (3 and 4). Sex ratio was 1.126 ± 0.27 in favour of males. Carapace width frequency distributions and weight‐at‐age data were used to estimate the von Bertalanffy growth equation parameters. For the population as a whole, these were: L∞ = 199 mm, W∞ = 1179.56 g, K = 0.24 year−1, t0 = −0.1004 years. The overall carapace width–weight relationship was: W = 0.38(CW2.69). Analysis of covariance indicated a significant difference in the carapace width–weight relationship between males and females in the study area. Total mortality Z and natural mortality M rates for combined sexes were 1.245 year−1 and 0.567 year−1, respectively. The exploitation ratio E was estimated to be 54.43%.